Sodium-Glucose Cotransporter 2 Inhibition for the Prevention of Cardiovascular Events in Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Arnott, C. (American Heart Association Inc., 2021)
10.1161/JAHA.119.014908